Tunisia : 2002 Article IV Consultation-Staff Report and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2002 Article IV Consultation highlights that the real GDP of Tunisia grew by 5 percent in 2001 compared with 4.7 percent in 2000, despite a contraction in agricultural output of 1.5 percent caused by a third consecutive year of drought. Activity was particularly robust in the mechanical-electrical industry, which grew by 14 percent, and the textile industry, which expanded by 12 percent. The authorities now face the challenge of reining in strong demand, which has put pressures on the external position and lowered foreign exchange reserves.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet